Expression pattern of Rheb gene in Jabal Barez Red goat - NOORI, AZRA NAJMI; BEHZADI, MOHAMMAD REZA BAHREINI; MOHAMMADABADI, MOHAMMAD REZA (The Indian Journal of Animal Sciences, 2017)
According to importance of Rheb gene on growth, cell cycle and cancer, expression of this gene for the first time was studied in Jabal Barez Red goat. Rheb belongs to Ras family that encodes a carboxylterminal CAAX box indicating that the protein may undergo post-translational farnesylation. Over-expressions of Rheb simulate cell growth while knockdown of Rheb expression, inhibits protein synthesis and cell growth. In this study, expression of Rheb gene was investigated by Real-Time PCR and Pfaffl method in various tissues including brain (medulla), brain (cortex), heart, kidney (cortex), kidney (medulla), testis, lung, liver and spleen. For analyzing the data of Pfaffl method, SAS software was used. Results showed that the Rheb gene was expressed in all the tested tissues and the highest level of expression was observed in spleen and the lowest level was detected in lung. Therefore, this gene is expressed in all the tissues and physiological effects of this gene needs to be investigated in different tissues and different animals.